2022
DOI: 10.1016/j.tem.2022.01.001
|View full text |Cite
|
Sign up to set email alerts
|

MANF: an emerging therapeutic target for metabolic diseases

Abstract: Mesencephalic astrocyte-derived neurotrophic factor (MANF) is an endoplasmic reticulum-resident protein and a secretory factor and has beneficial effects in multiple diseases. Recent evidence shows that its circulating levels in humans are dynamically regulated under various metabolic diseases, including diabetes, obesity, fatty liver, and cardiovascular diseases, suggesting that MANF may play a role in these pathological states. Also, its downregulation in mice impairs glucose homeostasis, promotes lipid accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 62 publications
0
17
0
Order By: Relevance
“…Consistent with MANF overexpression, these results demonstrated that exogenous supplementation MANF protected against lipid deposition and inflammation response, and inhibited SREBP1 and NF‐κB signaling with PA treatment, which indicated that exogenous supplementation MANF play a role in lipid metabolism and inflammation response at least in part. Previous studies proposed that extracellular MANF likely functions by three major pathways, including endocytosis, binding to its receptor NPTN and KDELR 20 . However, whether and how MANF acts in autocrine/paracrine manner will need more investigations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consistent with MANF overexpression, these results demonstrated that exogenous supplementation MANF protected against lipid deposition and inflammation response, and inhibited SREBP1 and NF‐κB signaling with PA treatment, which indicated that exogenous supplementation MANF play a role in lipid metabolism and inflammation response at least in part. Previous studies proposed that extracellular MANF likely functions by three major pathways, including endocytosis, binding to its receptor NPTN and KDELR 20 . However, whether and how MANF acts in autocrine/paracrine manner will need more investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies proposed that extracellular MANF likely functions by three major pathways, including endocytosis, binding to its receptor NPTN and KDELR. 20 However, whether and how MANF acts in autocrine/paracrine manner will need more investigations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a complex condition, MetS conditions often occurs together and elevates the risk of type 2 diabetes, prevalence of stroke and myocardial infarction, and mortality rate of cardiovascular diseases, as well as compromise life quality and cause great economic burden (3). Given the primary pathological components in MetS, including impaired glucose and lipid metabolism, the current treatments of healthy lifestyles changes, including improved dietary plans, regular physical activity, reducing stress, and stopping smoking are helping, but not enough (4)(5)(6). For the purposes of drug discovery, nuclear receptors (NRs) like peroxisome proliferator-activated receptor (PPARs), liver X receptor (LXRs), REV-ERBs, and retinoic acid receptor-related orphan receptors (RORs) have favorable attributes, with most containing protected internal cavities predisposed for occupation with hydrophobic molecules of volumes typical of drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, hypothalamus-specific enhancement of GDNF expression resulted in reduced food intake and body weight as well as increased energy expenditure in rats [8,9]. Mesencephalic astrocyte-derived neurotrophic factor (MANF) is a non-canonical neurotrophic factor that does not share any homology of its protein sequence with other canonical neurotrophic factors [10]. It was initially isolated from a rat mesencephalic type-1 astrocyte cell line and was shown to have neurotrophic effects 2 of 13 on dopaminergic neurons [11].…”
Section: Introductionmentioning
confidence: 99%